(3WQb LeY GdHjGfGJ h GdeYdheGJ dCZQGV GdHMK GdYdej (B/s - (3YdjGf, QHMj eUWais ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
(3eGgjI GdHjGfGJ h GdeYdheGJ , GdHMK GdYdej , GdedGMXI , GdebGHdI , GdGSJHGfI , eUGOQ GdeYdheGJ , GdecJHGJ h eQGcR GdeYdheGJ h OhQgG aj YedjI LeY GdeYdheGJ , THcGJ GdeYdheGJ , GdCfJQfjJ h GdecJHGJ GdGdcJQhfjI h OhQgG aj YedjI LeY GdHjGfGJ h GdeYdheGJ , GdYjfGJ (B.s
(3eQGLY U(B.251 (3; edGMb U(B.248((3GbJfGAGJ (B2014 2(3f(B)s
Keywords: (3GdHMK GdYdejs; (3JbfjGJ GdHMK GdYdejs; (3THcGJ GdeYdheGJs